2014
DOI: 10.1155/2014/987285
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs as a New Mechanism Regulating Adipose Tissue Inflammation in Obesity and as a Novel Therapeutic Strategy in the Metabolic Syndrome

Abstract: Obesity is associated closely with the metabolic syndrome (MS). It is well known that obesity-induced chronic inflammation plays a fundamental role in the pathogenesis of MS. White adipose tissue (AT) is the primary site for the initiation and exacerbation of obesity-associated inflammation. Exploring the mechanisms of white AT inflammation and resetting the immunological balance in white AT could be crucial for the management of MS. Several prominent molecular mechanisms have been proposed to mediate inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 91 publications
1
64
0
4
Order By: Relevance
“…Obese WAT displays classical signs of chronic inflammation, a key feature of obesity. Obesity leads to a chronic inflammatory state that is initiated and exacerbated in the WAT (Ge et al, 2014; Xu et al, 2003). For example, visceral adipocytes promote systemic inflammation by secreting mediators such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, and leptin, among others (Fontana et al, 2007).…”
Section: Adipose Tissue and Obesitymentioning
confidence: 99%
“…Obese WAT displays classical signs of chronic inflammation, a key feature of obesity. Obesity leads to a chronic inflammatory state that is initiated and exacerbated in the WAT (Ge et al, 2014; Xu et al, 2003). For example, visceral adipocytes promote systemic inflammation by secreting mediators such as interleukin (IL)-6, tumor necrosis factor (TNF)-α, and leptin, among others (Fontana et al, 2007).…”
Section: Adipose Tissue and Obesitymentioning
confidence: 99%
“…Unlike in many other species, including primates, known human miRNA coding sequences are located mostly in the introns of other genes; however, miRNAs coded in intergenic regions have been more frequently associated with human diseases (Ghorai and Ghosh 2014). Approximately 40 miRNAs have been found to influence adipogenesis (Son et al 2014) and many miRNAs contribute to the regulation of inflammation in white adipose tissue (Ge et al 2014). This group includes miR-31, which is produced by adipocytes and its expression has been found to increase after treatment by a macrophage LPS-conditioned medium, mimicking the inflammatory state (Ortega et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid/viral vectors encoding miRs are encouraging strategies to replace miRs in vivo, with good transduction efficiency and minimal toxicity (Brown et al, 2006, Colin et al, 2009). Therefore, the development of miR-based therapeutics is of great interest in various diseases (Banno et al, 2014, Boon et al, 2013, Ge et al, 2014, Kornfeld et al, 2013, Sun et al, 2012). In the present study, we found that miR-146b expression was significantly decreased in IL-10 deficient mice with colitis, which prompted us to test miR-146b mimic in the treatment of colitis in IL-10 −/− mice.…”
Section: Discussionmentioning
confidence: 99%